Exploring EFL Students’ Public Speaking Anxiety in Tertiary Level - Yunus, Annida Bandu; Syarif Amin; Faridawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study aims to find out the causes and strategies of English as a foreign language (EFL) students when they feel anxious to speak in public in certain situations. This research focuses on exploring EFL students from the English Education Study Program of Muhammadiyah Universities Kendari in the academic year 2023/2024. The sample of this study was taken by using purposive sampling technique, which was five students. The research instrument consisted of interview. After identifying the results of the interview, the researcher found two causes of student anxiety: Fear of negative evaluation and fear of communication specifically, three factors contributing to the fear of negative evaluation include fear of rejection, fear of answering questions, and feeling embarrassed. In addition, five factors associated with communication fear include mother tongue interference, the lack of preparation, language impairment, and the fear of comparison. Researcher also found several strategies used by students to reduce anxiety; Positive thinking, calming the mind and regulating breathing, practicing in front of a mirror, practicing talking with friends, preparing material can be concluded from the results of the five strategies is a lack of preparation.